Pengenalan Keterampilan Literasi Digital Pada Kelompok B di TK Negeri Pembina Ampenan - atun, Nurjahratun; Tahir, Muhammad; Jaelani, Abdul Kadir; Buahana, Baiq Nada (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to examine how digital literacy skills are introduced to Group B children, the extent of their digital literacy proficiency, and the challenges educators face when teaching these skills. One teacher and thirty-one Group B students at Taman Kanak-kanak Negeri Pembina Ampenan were selected as research subjects. A descriptive qualitative approach was employed to provide a factual and systematic description of the phenomena. Data were collected through structured interviews, documentation, and observation. The data analysis followed the interactive model by Miles and Huberman, which includes data collection, data reduction, data display, and conclusion drawing. The findings reveal that children demonstrated high enthusiasm when digital literacy skills were introduced through engaging and dynamic digital media, such as instructional videos and interactive stories directly supervised by the teacher. However, some children still required additional guidance to understand digital instructions and to stay focused when using digital media. The study concludes that the introduction of digital literacy skills to Group B at TK Negeri Pembina Ampenan was carried out effectively with teacher support, although challenges persisted, including limited teacher digital competence and children’s difficulty maintaining focus when interacting with digital media.